MORPHOMETRIC STUDY OF ANTERIOR HORN OF THE LATERAL VENTRICLE OF THE BRAIN AND ITS CORRELATION WITH AGE, GENDER, AND SIDE: A CROSS-SECTIONAL STUDY - Keshri, Ravi (Student's Journal of Health Research Africa, 2024)
Background The anterior horn of the ventricles undergoes peculiar changes as the brain ages. Enlargement of the ventricle horn has been associated with advanced aging. This study is conducted to analyze morphometric changes in the anterior horn of the lateral ventricles of both hemispheres. Method This was a cross-sectional study in which 250 computed tomography images of the brain were analyzed thoroughly. The anterior horn of the lateral ventricle was measured using a discomforts software. The age range of the participants was 20–80 years. Results The study revealed a significant increase in the size of the anterior horn of the lateral ventricle with advancing age, particularly prominent in the 61–80-year-old age group. The anterior horn was found to be larger in men compared to women, with the left side of the cerebral hemisphere showing greater enlargement than the right side. Specifically, the average length of the anterior horn on the right side was 28.72 ± 2.21 mm in men and 27.49 ± 2.31 mm in women. On the left side, the lengths were 29.92 ± 2.21 mm in men and 28.72 ± 2.41 mm in women. The differences between genders and sides were statistically significant. Conclusion The anterior horn of the lateral ventricle is prone to enlargement if it is from the left side, in the male gender, and as age increases, the enlargement of the ventricle horn becomes prominent. Recommendation while diagnosed with neurological diseases, enlargement of the lateral ventricles should be analyzed as per the age and gender of the patients.